Soybeans and Their Products : Markets, Models, and Policy - Houck, James P. (Book collections on Project MUSE., 1972)
This is the report of a comprehensive study designated to identify and measure empirically the forces, interrelationships, and processes which shape the behavior of the total soybean market. The research focused on the years from 1946 to 1967, a period wh.